PELAKSANAAN KEWAJIBAN PELAKU USAHA DALAM MENJALANKAN USAHA ANGKUTAN PENYEBRANGAN PASAR KAPUAS-SEBERANG KAPUAS DI KABUPATEN SEKADAU - NIM. A1011201101, PAUL BORNEWIR (Jurnal Fatwa Hukum, 2025)
ABSTRACTThis study discusses about boats or Crossing transportation in Sekadau Regency which still do not meet the standards of supporting facilities such as the lack of seats for passengers, the absence of life jackets, and also do not provide comfort for passengers because some ferry boats are not in a condition that is suitable for use. And do not have official tickets to guarantee insurance for passengers. The problems studied in writing this thesis are "What are the obligations of business actors in carrying out crossing transportation business activities in Sekadau Regency?" and "How is the supervision of business actors in carrying out crossing transportation business activities in Sekadau Regency?".  This study uses an empirical legal research method, namely by describing the conditions at the time of the study and analyzing them to draw conclusions. The nature of this research is descriptive. The data analysis used for the study is qualitative data analysis consisting of primary data in the form of interviews with service providers, then secondary data in the form of the Minister of Transportation Regulation Number PM 62 concerning Minimum Service Standards for Crossing transportation and Ministerial Regulation Number PM 61 of 2021 concerning the Implementation of Crossing transportation. Based on the results of the study related to the obligations of business actors in crossing transportation in Sekadau Regency, it is known that business actors have followed several rules provided by the Sekadau Regency Transportation Service in accordance with the Minister of Transportation Regulation No. 62 of 2019 concerning Minimum Services Standards for Crossing transportation, supervision should be carried out by the UPTD (Regional Technical Implementation Unit) in accordance with the Regulation of the Minister of Transportation Number PM 40 of 2022 concerning the Implementation of River and Lake Ports where the UPTD is tasked with preparing operational work plans and programs to provide business licensing services to shipping companies and ship operating permits for ferry crossings, but because the unit does not yet exist, the Transportation Agency is still taking over the role of supervision.Keywords: Crossing transportation, Obligations of business actors, Supervision.   ABSTRAK  Penelitian ini membahas tentang Perahu tambang atau perahu penyeberangan di kabupaten sekadau yang masih terlihat belum memenuhi standar fasilitas pendukung seperti kurangnya bangku untuk penumpang, tidak adanya pelampung,serta terlihat juga tidak memberikan kenyamanan bagi penumpang karena beberapa perahu tambang tidak dalam kondisi yang layak pakai. Serta tidak memiliki tiket resmi untuk menjamin asuransi terhadap penumpang. Adapun masalah yang diteliti dalam penulisan skripsi ini ialah "Bagaimana kewajiban pelaku usaha dalam mengadakan kegiatan usaha angkutan penyebrangan di kabupaten sekadau?" dan "Bagaimana pengawasan terhadap pelaku usaha dalam mengadakan kegiatan usaha angkutan penyeberangan di kabupaten sekadau ?". Penelitian ini menggunakan metode penelitian hukum empiris yaitu dengan menggambarkan keadan pada waktu penelitian dan menganalisa hingga mengambil kesimpulan. Sifat penelitian ini adalah deskriptif. Analisa data yang digunakan untuk penelitian adalah analisa data kualitatif yang terdiri dari data primer berupa wawancara kepada pemberi jasa, kemudian data sekunder berupa peraturan mentri perhubungan nomor PM 62 tentang Standar Pelayanan Minimal Angkutan Penyeberangan dan Peraturan Menteri Nomor PM 61 tahun 2021 tentang penyelenggaraan Angkutan penyeberangan.Berdasarkan hasil penelitian terkait kewajiban pelaku usaha pada angkutan penyeberangan di kabupaten sekadau diketahui bahwa pelaku usaha sudah mengikuti beberapa aturan yang diberikan oleh pihak Dinas perhubungan kabupaten Sekadau sesuai dengan Peraturan Menteri Perhubungan No. 62 Tahun 2019 tentang Standar Pelayanan Minimal Angkutan Penyeberangan terkait pengawasan seharusnya pengawasan dilakukan oleh UPTD ( Unit Pelaksana teknis Daerah) sesuai dengan Peraturan Mentri Perhubungan Nomor PM 40 tahun 2022 tentang Penyelengaraan Pelabuhan Sungai dan Danau yang dimana UPTD mengemban tugas menyusun rencana dan program kerja operasional memberikan layanan izin usaha kepada perusahaan pelayaran serta izin pengoperasian kapal untuk lintas penyeberangan, namun karena unit tesebut belum ada maka Dinas Perhubungan masih mengambil alih peran pengawasan tersebut  Kata Kunci: Angkutan Penyeberangan, Kewajiban pelaku usaha, Pengawasan.